EXPLORATION OF EGGSHELLS WASTE AS A SUSTAINABLE INTERIOR MATERIAL THROUGH MATERIAL-DRIVEN DESIGN (MDD) - Khevia Salsabilla Wibowo; Ully Irma Maulina Hanafiah; Dandi Yunidar (Adisam Publisher, 2026)
Food waste has become a pressing environmental issue within global sustainability discourse, yet it also holds significant potential as an alternative material resource. Among various food waste by-products, eggshell waste is abundant and rich in calcium carbonate, but remains largely underutilized in design contexts. Existing studies on eggshells predominantly focus on technical or performance based applications, leaving their experiential, aesthetic, and spatial potential underexplored. This study investigates the transformation of eggshell waste into a bio-based composite material for non-structural interior applications using the Material-Driven Design (MDD) framework. Adopting a practice-based design research approach, the study follows the full MDD sequence, encompassing material understanding, material characterization and experience, application vision, and material integration. Experimental exploration was conducted through variations in binder types, particle sizes, and mixing ratios, followed by surface finishing, color exploration, and tactile evaluation. The optimized material formulation was subsequently translated into a three-dimensional modular panel design and integrated with a lightweight metal framing system to examine its applicability within an interior context. The findings demonstrate that eggshell waste can be developed into a stable and expressive decorative surface material, where material behavior directly informs form, texture, and design decisions. By positioning eggshell waste as a design-active material, this research contributes to sustainable interior design discourse and highlights the relevance of Material-Driven Design as a methodology for transforming food waste into meaningful interior material applications.